EVALUATION OF THE SORPTION PROPERTIES IN CRAMBE KOCHIANA AND BUNIA ORIENTALIS (BRASSICACEAE B. FAMILY) ROOTS’ MEALS (Experimental biology, 2024)
The problem of environmental pollution is global and has multilateral consequences. One of them is the ingestion of toxicants into the human body with drinking water and food. Chronic intoxication with heavy metals poses an extreme danger to human health. In this regard, the development and search for ways to remove toxicants from the body and neutralize their adverse effects on the body does not lose relevance. Currently, based on numerous studies and practice, it can be argued that most of the plant raw materials and their waste is a source for obtaining various products, for example, dietary fibers, which are used as sorbents. Our study was aimed to evaluation of the sorption properties in  katran Kochiana and bunia orientalis roots’ meals on lead and cadmium salts. Studies have shown that the dietary fibers from the roots of these plants have sorption activity in relation to lead and cadmium ions. The roots of both plants had a greater affinity for cadmium ions, and it was also revealed that the sorption potential of the bunias roots' meals was slightly higher than that of katran Kochiana, although when examining samples for the presence of dietary fibers in the roots of bunia orientalis, their lower content was found.
Keywords: sorption, heavy metals, dietary fibers, sorption capacity, equilibrium constant